6 - Correlation Of Cardiorespiratory Fitness And Cognitive Response In School Children (Fiep Bulletin - online, 2021)
Introduction: The predominance of cardiovascular risk conditions has resulted in major health challenges, also becoming a cause of attention in the infant-juvenile population. It is understood the cognition, as perception, learning, memory, attention, surveillance, reasoning and problem solving. It is worth mentioning that the psychomotor functioning (reaction time, movement time, performance speed) has frequently related in this concept. Objective: To evaluate the correlation of cardiorespiratory fitness in cognitive function in male school children. Methodology: This is a cross-sectional study with 20 male students. The Body Mass Index (BMI) and the VO2MÁX were analyzed by means of the Manual of Proesp-BR and memory and Tangram tests were performed. The results were analyzed through mean and standard deviation in the SPSS 20.0 program. Results: The mean age of the schoolchildren was 10.75 ± 1.02 years old, with a height of 1.43 ± 0.78 meters, related to the weight of the schoolchildren, we obtained a mean of 40.71 ± 9.90 kg. Only 5% (n=1) stayed in the healthy zone, with the test result of (1003.4ml/kg-min),and 95% (n=19) stayed in the risk zone, with the average result of the VO2MÁX test in 748.6 ± 90.2ml/kg-min. The mean BMI was 19.73 ± 4.28 kg/m². Conclusion: Based on the results found, it is concluded that a good cardiorespiratory capacity is linked to an improvement in the cognitive response of the tests performed